2021
DOI: 10.1021/jacs.1c05762
|View full text |Cite
|
Sign up to set email alerts
|

Total Synthesis of the Chlorinated Pentacyclic Indole Alkaloid (+)-Ambiguine G

Abstract: Reported herein is the total synthesis of (+)-ambiguine G, the first member of the chlorinated pentacyclic ambiguines to yield to chemical synthesis. The synthesis is accomplished through a convergent strategy that proceeds in 10 steps from ( S )-carvone oxide. Pivotal to the concise route is the successful realization of a [4+3] cycloaddition that conjoins two easily synthesized components of the carbon framework of the natural product. Also featured in the synthesis is the efficient, d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 33 publications
(32 reference statements)
0
3
0
Order By: Relevance
“…Efficient and straightforward installation of a vinyl group holds significant importance in contemporary organic synthesis due to its prevalence in natural products and its versatility for subsequent derivatization reactions (Figure ). In particular, our interest in natural products in the hapalindole family, such as N -methylwelwitindolinone D isonitrile and ambiguine G, impressed upon us the absence of a simple, general method for the direct introduction of an vinyl unit α to a carbonyl group. , This is a long-standing problem, and two distinct strategies have been developed to address it: (1) the use of various vinyl cation equivalents as electrophiles and (2) the direct coupling with different alkene and alkyne derivatives. The first strategy has been the subject of extensive exploration, and a diverse range of vinyl group precursors have been developed, including α-phenylselenylacetaldehyde, trimethylsilyl-aldehydes, phenyl vinyl sulfoxide, and vinyl ether–iron complexes (Figure A) .…”
Section: Introductionmentioning
confidence: 99%
“…Efficient and straightforward installation of a vinyl group holds significant importance in contemporary organic synthesis due to its prevalence in natural products and its versatility for subsequent derivatization reactions (Figure ). In particular, our interest in natural products in the hapalindole family, such as N -methylwelwitindolinone D isonitrile and ambiguine G, impressed upon us the absence of a simple, general method for the direct introduction of an vinyl unit α to a carbonyl group. , This is a long-standing problem, and two distinct strategies have been developed to address it: (1) the use of various vinyl cation equivalents as electrophiles and (2) the direct coupling with different alkene and alkyne derivatives. The first strategy has been the subject of extensive exploration, and a diverse range of vinyl group precursors have been developed, including α-phenylselenylacetaldehyde, trimethylsilyl-aldehydes, phenyl vinyl sulfoxide, and vinyl ether–iron complexes (Figure A) .…”
Section: Introductionmentioning
confidence: 99%
“…In this context, highly reactive dearomatized indole frameworks display a privileged role in nature as well as in chemical synthesis (Scheme A). For example, Martin and Rawal et al found that 2-methide-2 H -indoles rapidly undergo efficient (4 + 3) cycloadditions with electron-rich dienolsilanes to furnish racemic cyclohepta­[ b ]­indoles, which were further applied to the nonasymmetric synthesis of natural products actinophyllic acid and ambiguine P …”
mentioning
confidence: 99%
“…The (4 + 3) reaction of C3-indolyl cations (route A) was realized by Wu and co-workers, and its enantioselective version was developed by Masson et al using Brønsted acid catalysis . The related reaction wherein the C2-indolyl cation is intercepted by a diene has also been studied, and it provided the basis for Martin’s elegant synthesis of actinophyllic acid as well as our recent syntheses of ambiguines P and G. ,, The chiral Brønsted acid-catalyzed enantioselective version of the reaction was recently reported by List et al The second pair of disconnections (routes B and B′), which had not been reported when we commenced our studies, involve the reaction of a three-carbon dipole such as an oxyallyl cation or its equivalent with either 2- or 3-alkenyl indoles. , Notably, in 2020, Rossi and co-workers reported a comprehensive study demonstrating the successful realization of route B . Given our interest in the ambiguines, we directed our attention to routes that offered the possibility for the direct introduction of the gem-dimethyl groups on the carbon attached to the indole C2 position.…”
mentioning
confidence: 99%
“…Our longstanding interest in the hapalindole family of cyanobacteria metabolites drew our attention to its pentacyclic ambiguine subset, exemplified by ambiguines P and G (Figure ). Embedded in their complex architectures is a cyclohepta­[ b ]­indole unit, which is also present in many other natural products and in leads to pharmaceutical drugs, examples of which are shown in Figure . Indeed, due to its prevalence in bioactive compounds, cyclohepta­[ b ]­indole has been recognized as a “privileged” unit for drug design and has motivated the development of assorted methods for its synthesis .…”
mentioning
confidence: 99%